Sharing superior crop varieties with local farmers in the Solomon Islands - Tikai, Pitakia (Technical Centre for Agricultural and Rural Cooperation, 2018)
In 2006, the Kastom Gaden Association (KGA) recognised the need to diversify the Solomon Islands’ crop varieties in order to combat the strain that an increasing population was having upon people’s livelihoods. The 3-year Searem Niu Plant Long Gaden project sought to introduce African yam, cassava and sweet potato varieties from overseas and this established a process of crop diversification which improved the country’s self-sustainability.